2010
DOI: 10.1142/s0218216510008455
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsically Knotted Graphs Have at Least 21 Edges

Abstract: We prove that every intrinsically knotted graph has at least 21 edges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 8 publications
0
24
0
Order By: Relevance
“…With this in mind, we concentrate on triangle-free graphs in this paper. It is known [3,4,10] that K 7 and the 13 graphs obtained from K 7 by ∇Y moves, Johnson, Kidwell and Michael [7], and, independently, Mattman [12] showed that intrinsically knotted graphs have at least 21 edges. Recently two groups, working independently, showed that K 7 and the 13 graphs obtained from K 7 by ∇Y moves are the only minor minimal intrinsically knotted graphs with 21 edges.…”
Section: Introductionmentioning
confidence: 99%
“…With this in mind, we concentrate on triangle-free graphs in this paper. It is known [3,4,10] that K 7 and the 13 graphs obtained from K 7 by ∇Y moves, Johnson, Kidwell and Michael [7], and, independently, Mattman [12] showed that intrinsically knotted graphs have at least 21 edges. Recently two groups, working independently, showed that K 7 and the 13 graphs obtained from K 7 by ∇Y moves are the only minor minimal intrinsically knotted graphs with 21 edges.…”
Section: Introductionmentioning
confidence: 99%
“…Johnson et al. and, independently, the second author showed that intrinsically knotted graphs have at least 21 edges. Hanaki et al.…”
Section: Introductionmentioning
confidence: 99%
“…The only bipartite graph in this set is C 14 , the Heawood graph. As graphs of 20 edges are not intrinsically knotted , C 14 is minor minimal for intrinsic knotting and, so, also for bipartite intrinsically knotted. By Theorem , if G=22, G must be one of the two cousins in the E9+e family.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As part of their proof that intrinsic knotting requires 21 edges, Johnson, Kidwell and Michael [5] showed that every triangle-free graph on 20 or fewer edges is 2-apex and, therefore, not knotted. In the current paper, we show: This suggests the following: Question 1.5 Is every non-IK graph 2-apex?…”
Section: Introductionmentioning
confidence: 99%